Discrepancy between training, competition and laborytory measures om maximum heart rate in NCCA Division 2 distance runners - Semin, K.; Stahlnecker, A. C.; Heelan, K.; Brown, G. A.; Shaw, B. S.; Shaw, I. (Journal of Sports Science & Medicine, 2008)
A percentage of either measured or predicted maximum heart rate is commonly used to prescribe and measure exercise intensity. However, maximum heart rate in athletes may be greater during competition or training than during laboratory exercise testing. Thus, the aim of the present investigation was to determine if endurance-trained runners train and compete at or above laboratory measures of 'maximum' heart rate. Maximum heart rates were measured utilising a treadmill graded exercise test (GXT) in a laboratory setting using 10 female and 10 male National Collegiate Athletic Association (NCAA) division 2 cross-country and distance event track athletes. Maximum training and competition heart rates were measured during a high-intensity interval training day (TR HR) and during competition (COMP HR) at an NCAA meet. TR HR (207 ± 5.0 b·min-1; means ± SEM) and COMP HR (206 ± 4 b·min-1) were significantly (p < 0.05) higher than maximum heart rates obtained during the GXT (194 ± 2 b·min-1). The heart rate at the ventilatory threshold measured in the laboratory occurred at 83.3 ± 2.5% of the heart rate at VO2 max with no differences between the men and women. However, the heart rate at the ventilatory threshold measured in the laboratory was only 77% of the maximal COMP HR or TR HR. In order to optimize training-induced adaptation, training intensity for NCAA division 2 distance event runners should not be based on laboratory assessment of maximum heart rate, but instead on maximum heart rate obtained either during training or during competition.